Legislative reform of warranties in South African marine insurance law - Brown, Gavin (Centre for Law and Society, 2026)
In South Africa, because of its historical connection with England, it is English law that has come to be applied in the context of insurance. One aspect of English insurance law that has come to be particularly criticised over time is the approach to warranties as specific and unique clauses in insurance contracts. The vociferous nature of the calls for change and the fact that their inequity • has been identified by both courts and commentators for over a hundred years is an indication of the need for change. This paper takes this need for change as its starting point, going on to consider what legislative reform is needed in South Africa to restore order to a particularly untidy area of insurance law. To do this, this paper will set out the application of warranties in South African insurance law by following their development in English law and their complicated reception into our own.